Literacy Teachers' Interactions with Instructional Leaders: Students Reap the Benefits - Gary Alger (Arizona State University, 2015)
This paper examines the interactions between literacy teachers and instructional leaders and their effects on students reading achievement gains. The results of this study have implications for how instructional leaders work with colleagues and how these relationships may impact student achievement. Forty-two suburban elementary and middle school literacy teachers reported the frequency and helpfulness of interactions with their instructional leaders. Findings indicate that curricular and assessment interactions occurred more frequently and were more helpful than instructional interactions. Students of these teachers who reported the most frequent and helpful interactions had significantly higher reading achievement gains than students of teachers who reported the least frequent and least helpful contacts.